Determinants of Employee Performance Mediated by Organizational Commitment - Endang Saefuddin Mubarok; Ronita; Euis Bandawati (Yayasan Ilomata, 2021)
The research aimed at determining the effect of training, work motivation, financial compensation on the performance of employees in Makasar Subdistrict, East Jakarta Timur, mediated by organizational commitment. The path analysis with descriptively and explanatorily-quantitative method was used for planning this research. The samples were 81 respondents by using the sampling method. According to the significance levels, the results of the research indicated that: (1) Work motivation, financial compensation, and training had a significant effect on organizational commitment; (2) Work motivation, financial compensation, training had a significant effect on employee performance, either directly or mediated by organizational commitment; and (3) Organizational commitment had a significant effect on employee performance.